Новый пухоед рода Philopterus (Mallophaga, Philopteridae) с сероголовой гаички из Якутии - Федоренко, И.А.; Васюкова, Т.Т. (Вестник зоологии, 1985)
Philopterus taigensis sp. n.- allied to Ph. rutteri from Parus montanus, differs by larger body size, head shape, presence of three pleural chetae in each upper angle of IX abdominal segment in female.